Non-invasive monitoring of subclinical and clinical actinic keratosis of face and scalp under topical treatment with ingenol mebutate gel 150 mcg/g by means of reflectance confocal microscopy and optical coherence tomography: New perspectives and comparison of diagnostic techniques. - Ruini, Cristel; Hartmann, Daniela; Bastian, Mike; Ruzicka, Thomas; French, Lars E.; Berking, Carola; Von Braunmuehl, Tanja (Journal of Biophotonics, 2019)
Actinic keratosis (AK) corresponds to the earliest stage of in situ squamous cell carcinoma and arises on chronically sun-exposed skin. Around the clinically evident AKs, the apparently healthy epidermis may contain different grades of atypia that can be detected by noninvasive imaging techniques such as reflectance confocal microscopy (RCM) and optical coherence tomography (OCT). Subclinical actinic keratosis (sAK) has captured increasing interest as a potential target of field therapies. The aim of this study was to evaluate in vivo the changes in the field cancerization undergoing treatment with topical ingenol mebutate by combining RCM and OCT. Twenty patients with field cancerization of the face and scalp were treated with ingenol mebutate gel (150 mcg/g) for three consecutive days on an area of 25 cm2 containing at least two AKs, two sAKs and two apparently healthy sites. About 120 lesions were evaluated through clinical investigation and clinical, dermoscopical, RCM and OCT images at day 0, 4, 14 and 56 based on the diagnostic criteria for AKs. Main pathological features improved in both AKs and sAKs, in particular the epidermal thickness measured by OCT and the epidermal atypia graded by RCM. Local skin reactions (LSR) arose predominantly in the lesional area compared with healthy skin. A complete clearance was detected in 58% for AKs, and in 55% and 72% for sAKs measured by RCM and OCT, respectively. Both OCT and RCM allow the morphological representation of field cancerization including subclinical lesions and provide complementary information. Ingenol mebutate is effective not only in clinically evident but also in sAKs. The differences in LSR highlight the potential selectivity of the treatment.
EVALuna2:210468